Problems of The Teacher Profession In Indonesia (Review From The Perspective of Law Number 14 of 2005) - Mukhamad Saekan (Green Publisher Indonesia, 2023)
The Teacher profession is carried out through planning, implementing and evaluating learning. Teachers are called professionals if they are able to carry out learning properly and correctly which is shown by the skills to carry out learning techniques, methods, approaches and strategies properly and correctly. Every hour of learning The teacher must be in the school, if at the time of school hours being outside the school without justifiable reasons is categorized as having committed a violation of the teaching profession. The purpose of this study is to determine the problems of the teacher profession in Indonesia. By using the PTK research method carried out in schools. The results obtained are that the professionalresponsibility of teachers is carried out through planning, implementing and evaluating learning in schools. Consequently, therefore teachers must have a variety of knowledge and skills and have a sense of security and comfort in carrying out their professional duties.